Frequency of Diabetic Nephropathy in Type 2 Diabetic Patients Using Spot Urine ACR and Its Associated Risk Factors - Asad Ullah; Sayed Ali Zeeshan Kausar; Muhammad Ayaz; Muhammad Shabbir Khan; Sami Ullah; Rida Fatima Saeed (Life and Science)
Objective: To determine the frequency of diabetic nephropathy in type 2 diabetic patients using spot urine ACR ratio and identify its associated risk factors. Study Design: Descriptive, cross-sectional study. Place and Duration of Study: This research was carried out at the Department of Medicine, Muhammad Teaching Hospital (MTH) Peshawar, Pakistan from February 01, 2023, to July 31, 2023. Methods: A total of 150 patients having type 2 diabetes mellitus were investigated. The sample size was calculated with a WHO sample size calculator using a reference study with a 10.8% prevalence of diabetic nephropathy in individuals with type 2 diabetes mellitus; confidence interval = 95% and the margin of error was 5%. Results: With an SD ± 5.146, the mean age was 49 years old. There were 87 (58%) females and 63 (42%) males present. Out of 150 individuals, the spot urine ACR was analyzed. Of these, 47 (31%) had microalbuminuria (less than 300 mg/m) while, 28 patients (19%) had macroalbuminuria (more than 300 mg/m), whereas end-stage renal disease was found in 6 (4%) with GFR < 30 ml/m -1.73 m2. A study was conducted on 150 individuals to determine the status of diabetic nephropathy. Of these, 81 (54%) had diabetic nephropathy and 69 (46%) did not. Conclusion: Using the spot urine ACR ratio, our study suggests that 46% of type-2 diabetic patients had diabetic nephropathy. The incidence was 24% in people with diabetes for 5–10 years and 26% in patients with diabetes for 11–15 years. Patients with diabetes for 16 to 20 years had a 50% incidence. In conclusion, those with diabetes for a longer period are at a much greater risk of diabetic nephropathy.